Severe and Fatal Fentanyl Poisonings from Transdermal Systems after On-Skin and Ingestion Application - Karina Sommerfeld-Klatta; Wiktoria Jiers; Magdalena Łukasik-Głębocka; Artur Tezyk; Klaudia Dolińska-Kaczmarek; Kamil Walter; Paweł Świderski; Szymon Rzepczyk; Barbara Zielińska-Psuja; Czesław Żaba (Toxics, 2023)
In recent years, the administration of fentanyl (FNTL) implicitly in transdermal drug delivery systems (TDDS) has vastly increased in chronic pain treatment. Non-medical and uncontrolled use of FNTL in TFDS (transdermal fentanyl delivery systems) may reveal toxic effects by the route of exposure, dermal or alternative, by ingestion of patches, and drug release in the stomach. The purpose of this study was to present three different cases of FNTL poisonings, two of which resulted in death due to TFDS abuse. The first case is a 66-year-old woman treated for accidental FTNL poisoning resulting in acute respiratory distress syndrome. Two remaining cases are a 31-year-old woman and a 25-year-old man who died as a result of FNTL overdose after on-skin and ingestion application of the drug patches. During the hospitalization of the 66-year-old patient, in blood samples, FNTL was confirmed at a concentration of 10.0 ng/mL. Tests run on blood taken from the corpses of 25- and 31-year-old patients exhibited FNTL presence in concentrations of 29.1 ng/mL and 38.7 ng/mL, respectively. The various routes of administration and ultimately toxic effects are important to present because, in TDDS, fentanyl can be a reason for severe to fatal poisoning, as shown by the three cases above.